Hubungan mekanisme koping dengan tingkat kecemasan pada pasangan infertil di RSIA Annisa Jambi tahun 2015 - bri novrika (Riset Informasi Kesehatan, 2017)
Anxiety can be an important factor in the decision to seek, continue, or stop the treatment of infertility. The anxiety level of the infertile couple varies and is influenced by coping and adjustment mechanisms. This study aims to determine the relationship of coping mechanism with anxiety level in infertile couples at RSIA Annisa Jambi.The type of this study was cross sectional, with a sample of 76 female infertile couples who experienced anxiety with total sampling technique. Data analysis with chi square test.The result of this research is correlation of coping mechanism (p = 0,000) with anxiety level on infertile couple.It is expected that hospitals providing infertility treatment services to provide therapy through psychiatric nursing psychoeducation therapy and / or supportive therapy to infertile couples so as to assist in minimizing the anxiety experienced and support the treatment program undergone infertile couples